Consumer responses to savings message framing. (September 2020) - Yang, Bi; Mattila, Anna S.
Abstract: Despite the prevalent use of savings messages (e.g., "get x off" and "save x"), no previous tourism and hospitality research has examined their effect on consumer responses. To fill that void, this study investigates the joint effect of savings message type (gain-framed vs. nonloss-framed) and weather conditions (sunny vs. rainy) on consumer attitude. The results show that individuals in rainy weather respond more favorably to a gain-framed (vs. nonloss-framed) message, and this effect is attenuated among people in sunny weather. Furthermore, this study reveals a boundary condition. When the amount of savings is presented in percentage terms (e.g., "get x% off" and "save x%"), the superiority of a gain frame disappears. Theoretical and managerial implications are discussed. Highlights: Weather impacts the efficacy of gain-framed and nonloss-framed savings messages. A "get x off" (vs. "save x") message is more effective in rainy weather. The two savings messages are equally effective in sunny weather. A "get % off" message is not superior to a "save %" cue in rainy weather.